Analisis Komponen Tutur Pada Iklan Lowongan Kerja Di Surat Kabar Kedaulatan Rakyat Edisi Februari 2017 Dan Relevansinya Sebagai Bahan Ajar Bahasa Indonesia Di SMK - Daryanti, Daryanti; , Dra. Atiqa Sabardila, M. Hum (2017)
ABSTRACT The purpose of this study is to, (1) identify patterns of sentence on job advertisements in the newspaper People's Sovereignty issue of February 2017, (2) analyzing the components said in the newspaper People's Sovereignty issue of February 2017, (3) and describes the relevance of the ad text job as teaching materials Indonesian on the material to write a job application letter class XII students. The method used in this research is qualitative method. This research was begun from February 2017 to May 2017. The technique of gathering information in this research uses listening and writing technique. To analyze the data in this study used referral pad technique, technique change, engineering change intentions, and technical editing on the method agih. There are three result of this research. One, 73 sentence of 25 the amount of data being analyzed in the newspaper People's Sovereignty issue of February 2017. Two, are 7 gathering information seech act 4, 5, 10, 12, 13, 14, 16, and 24. Except gathering information mention speech act not complete. Three, form relevance matter lesson, student ask surgical operation the newspaper People's Sovereignty issue be based on speech act and patterns of sentence inside later stack letter proposal work bebased on advertisement. Keywords: discourse, advertising, sentence patterns, and speech components.